(untitled) (Trabalho & Educação, 2016)
Workers professional formation is impacted by daily apprenticeships, more or less invisible, acquired in different social spheres. Two of these spheres, the school and the production, are particularly significant for structuring knowledge and for the constitution of work values. They are formative loci with distinct purposes and singular characteristics. They represent the field where the relationship between education and work is materialized, translating a complex dynamic between different rationalities and reflecting the capitalist societies contradictions. Based on this field, this study is dedicated to investigate the articulation between the conceptual dimension of pedagogy and the work praxis, aiming at understanding the formation processes in vocational and technological education. The examination of the work activity... ___ A formação profissional de um trabalhador é impactada por aprendizagens, mais ou menos invisíveis, decorrentes do viver cotidiano nas diferentes esferas sociais. Duas dessas esferas, a escolar e a da produção, são particularmente importantes na estruturação de saberes e na constituição de valores pertinentes ao mundo do trabalho. São espaçosformativos com finalidades distintas e características próprias. Representam o campo onde se materializa a relação entre educação e trabalho, traduzindo uma complexa dinâmica entre distintas racionalidades e refletindo as contradições inerentes às sociedades capitalistas. É com base nesse campo que este estudo se volta à investigação da articulação da dimensão conceitual da pedagogia com a práxis do trabalho, visando ao entendimento dos processos formativos na educação profissional e tecnológica – EPT. O exame da atividade de trabalho...